Parenting Patterns to Farmer’s Children - Enggal Hadi Kurniyawan (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
Parents who work as farmers have little time to care for their children. Most of the farmers spend their time in the fields where they work. The attitude of parents who are indifferent to their children can have a negative impact on a child, starting from a physical and psychological perspective. The various parenting styles applied to farmer parents with low levels of education also mean that many children do not get proper education so that they will also be employed in the fields to become successors of their parents' work as farmers and have the potential to marry early. This study aims to determine the role of farmer parents in providing parenting styles for children and also the types of parenting styles used by farmers for their children. This research method uses a method that is carried out with comprehensive research and contains interpretations of the results of the literature that have a relationship with certain topics using a systematic approach. The results of this study indicate that there are many roles played by farmer parents in raising children, starting from financing children's needs, developing children's socio-emotionality and facilitating children to develop their interests and talents. Meanwhile, the type of parenting that is widely used by farmer parents is democratic parenting.